Peran Suami dalam Penggunaan Alat Kontrasepsi yang Berwawasan Gender - Anggraeni, Mekar Dwi; Hartati,; Permana, Ryan Hara (Jurnal Keperawatan Soedirman, 2007)
Public opinion stated that the choices of using contraception tool are women responsibility. Based on the statistical data from Puskesmas Purwokerto Timur, 85 % birth control acceptors are women. Basically, the choices of birth control methods are married couple responsibility. The purpose of this study was to show the men participation in using birth control methods. This study was descriptive survey with case study. This study performed at Puskesmas Purwokerto Timur. The criteria of respondent were married couple who has joined family planning program for 6 moths or more. Data were taken by using questionnaire with several questions in terms of men participation of birth control methods. The result show that the number of birth control acceptor by using pills, hormone injection, implant, tubektomi, IUD and condom at 41 (45.55%), 23 (25.55%), 7 (7.77%), 3 (3.33%), 14 (15.55) and 2 ( 2.06 %) respectively. The participation of men in family planning program is only 2.06 %. In summary, the percentage of men participation in family planning program at Puskesmas Purwokerto Timur is very low